If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -5 = 5x + -47 Reorder the terms: -5 + 11x = 5x + -47 Reorder the terms: -5 + 11x = -47 + 5x Solving -5 + 11x = -47 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -5 + 11x + -5x = -47 + 5x + -5x Combine like terms: 11x + -5x = 6x -5 + 6x = -47 + 5x + -5x Combine like terms: 5x + -5x = 0 -5 + 6x = -47 + 0 -5 + 6x = -47 Add '5' to each side of the equation. -5 + 5 + 6x = -47 + 5 Combine like terms: -5 + 5 = 0 0 + 6x = -47 + 5 6x = -47 + 5 Combine like terms: -47 + 5 = -42 6x = -42 Divide each side by '6'. x = -7 Simplifying x = -7
| 19=-5v-1 | | 3(2x)+4(6)-6x=-2(2x+2)+4 | | 4b+3b-2=19 | | 9x-6=3x+4 | | =8-2y | | 2(5x+12)-10x=-4(3x+3)+12 | | 6=4+5 | | 180=-4(3x-4)-16 | | 6z+z^2=16 | | 8b-2=2b+4 | | -8=2(x-5)+10 | | Log(5)(3x-2)=2 | | 7e^6x=193 | | ln(15x)-2ln(1+x)=ln(3) | | 7(3+y)=6(y-4) | | 5x+35=16 | | bx=ax+c | | tan(2B+10)=cot(4B-10) | | 4x+10=23x | | 13-4x=4x+5-6x | | -2=-5x-5+6x | | 3u=-34-2u | | b^2+6b(0.5)=36 | | 30(2/15) | | 30•2/15 | | 24=6b-4 | | 13=6(x-7)+8 | | 6x+7=2x-37 | | 7b+4a-3a-5b= | | 1.1666x=140 | | 37=5+8x | | 3512/4= |